Double peeling of elastic pre-tensioned tapes (Fracture and Structural Integrity, 2014)
Peeling is a physical mechanics involved in the detachment of many natural and industrial applications. In this paper, we investigate the double peeling of an endless elastic pre-stressed tape adhering to a flat smooth rigid substrate. Solutions are given in closed form and their stability is discussed. Critical pull-off force needed to detachment is shown to be higher for pre-stressed tapes. However, when a pre-stress is high, tapes behave differently and may spontaneously detach from the rigid substrate.
Keywords: Peeling